A comparative analysis of the lay-friendliness of Danish EU patient information leaflets from 2000 to 2012. (27th January 2016) - Askehave, Inger; Korning Zethsen, Karen
Abstract : Since becoming mandatory in the EU in 1992, the patient information leaflet (PIL) has been the subject of an on-going discussion regarding its ability to provide easily understandable information. This study examines whether the lay-friendliness of Danish PILs has improved from 2000 to 2012 according to the Danish consumers. A reproduction of a questionnaire study from 2000 was carried out. The responses of the 2012 survey were compared to those of the 2000 survey and the analysis showed that Danes are less inclined to read the PIL in 2012 compared to 2000 and that the general interest in PILs has decreased. The number of respondents who deem the PIL easy to read has gone down. According to Danish consumers, the lay-friendliness of PILs has not improved from 2000 to 2012 and a very likely explanation could be that the PIL as a genre has become far too regulated and complex to live up to its original intentions. On the basis of the empirical results the article furthermore offers suggestions for practice changes.